Assessing the Extraction Potential of Tomsk Region’s Difficult-To-Obtain Oil Reserves - Sharf, Irina Valeryevna; Grinkevich, Larisa Sergeevna (Economy of Regions, 2016)
A significant increase in oil production in the Tomsk region can be achieved by a better development of the license areas at the disposal of oil-producing companies, active prospecting, introduction of innovative technologies to increase the oil recovery, as well as active oil extraction from unconventional horizons. This article reviews the activities of the oil-producing companies of the Tomsk region for the past 10 years, and proves the potential of increasing oil production of both traditional and difficult- to-obtain oil reserves, concentrated in the Bazhenov and Tyumen Formations and the Lower Jurassic sediments. Technologically, Russia is significantly lagging behind the economically developed countries in the extraction of hard unconventional hydrocarbon resources, primarily, the United States. The observed «shale revolution» was due to the complex of financial and tax breaks for oil companies, from which mainly medium and small companies were benefited. As a result, this requires an increase in investment on the part of economic entities and regional authorities, as well as additional tax benefits, considering the quality and types of actual and prospective raw materials produced in the region, in contrast to the declared benefits in Eastern Siberia. The introduction of tax incentives justified by the authors and the implementation of public-private partnership will ensure the profitability of the development of marginal and difficult-to-obtain oil deposits of the Tomsk region in the long term, which in turn should ensure the stability of economic development of the subject of the Russian Federation.